IMPOLITE READER RESPONSES ON ONLINE NEWS COMMENTS IN VIVA.CO.ID - Mia Rizana; Sri Minda Murni; T. Thyrhaya Zein (Universitas Negeri Medan, 2018)
The objective of this study was to discover the realizations of impolite utterances used by the readers as their responses on online news comments in viva.co.id news site. The study was conducted by using qualitative descriptive which case study was used in order to describe the impolite readers responses in viva.co.id news site. The data of this study were words, phrases, clauses and sentences consist of impolite reader response on online news comments in viva.co.id which the data were taken from 22 titles of political news about Basuki Cahaya Purnama . The data were the reader’s utterances on online news comments in political news in order to find out the recurrence and the pattern of the data based on the problem of the study. It was found that impolite utterances were realized by online news readers through disinterested, unconcerned, unsymphatetic; inappropriate identity markers; abscure or secretive language; seek disagreement; taboo words; call the other names; frighten; condescend, scorn of ridicule; negative personalize; disassociate from others and insult. Keywords: Impolite Utterances, Realization of Impoliteness